MODELO DE REGRESIÓN LOGÍSTICA - Hurtado Dianderas, Eulogio (2007)
ABSTRACT The Logistic subjet of Operations and constitutes a fundamental element in the academic formation of Magíster in Administration since it provides to the student the necessary tools for the decision making in the areas of supplyings, I transport and communications in all company. The present articulate present deals with on the development and application about a model logistic regression that contributes the knowledge for one better administration of the material resources with the due quality, amount required costs and opportunity.